Empoderamento feminino: a participação e experiência da mulher no ecoturismo e no turismo de aventura no RN - Batista, Francyane Gleice do Nascimento (2021)
Tourism activity combined with empowerment has offered liberating experiences for women, even though many of them need to face challenges in order to experience them. Thus, the study aims to analyze how Ecotourism and Adventure Tourism provide empowerment experiences for women who participate in these activities, in the state of Rio Grande do Norte. The research is characterized as exploratory-descriptive with a qualitative approach, data collection was based on interviews with participants in Ecotourism and Adventure Tourism activities offered by Agência Z (the real name of the agency has been omitted). In addition, the interviews were based on bibliographic research on the topic. Some results of the research identified that women who participate in adventure activities feel empowered in all aspects, being they social, economic, psychological and political.